Empirical Effects of Work Environment, Job Satisfaction and Work Engagement On Turnover Intention in Hospitality Industry - Andriani, Rian; Disman , Disman; Ahman, Eeng; Santoso, Budi (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
This study aims to analyze the effect of the work environment on turnover intention, by employing the mediating role of job satisfaction and work engagement. A poor work environment is more likely to increase turnover intention, and our study aims to mitigate this effect by using the effects of job satisfaction and work engagement. The study was conducted on hotel employees in Bandung City, West Java, Indonesia. The analytical technique used is the partial least squares method to test the significance of the relationship between research constructs. The results showed that supportive work environment has positive effects on job satisfaction and on employee work engagement. In relation with the effect of job satisfaction, the findings demonstrated its positive and significant influence on employee work engagement. Regarding the turnover intentions, the results found a negative and significant effect of work engagement on employee turnover intention. Mediation analysis reveals the important role of job satisfaction in mediating the relationship between work environment and turnover intention. The conclusion of these findings underscores the role of supportive work environment, increased employee engagement and satisfaction as important antecedents in minimizing turnover intention in the hotel industry. The practical implication for hotel managers is to ensure the active and participatory engagement of employees while remaining focused on creating a supportive and satisfying work environment. Keywords: hospitality, job satisfaction, turnover intention, work engagement, work environment